Evaluation of Generating DNA Profile from Keratinous Tissues - M. Al-Zubaidi, Mohammed; Jasim Sheha, Miriam; Younis Salih, Thoalnoon; Sadeq Ameen, Rasha (Al-Nahrain Journal of Science, 2026)
Fragmented DNA samples became serious issue in crime scene and all most result in incomplete DNA profile. Keratinous tissues such as hair and nails contain highly fragmented DNA and could be seen as biological evidence at crime scene. This study aimed to evaluation of generating DNA profile from keratinous tissues. Ten samples (five from hair and five from nails) collected from volunteers. Extraction of DNA was carried out by using PrepFilerTM forensic DNA extraction kit. The quantities of DNA were measured using real-time PCR, while the amplification of eight loci (D13S31, D7S820, D2S1338, D21S11, D16S539, D18S51, CSF1PO, FGA) and amelogenin was performed using the AmpFLSTR™ MiniFiler™ PCR Amplification Kit. The genetic Analyzer 3130 XL system and GeneMapper ID software v.3.2 were used to perform capillary electrophoresis and data analysis. The results indicated that the mean quantities of DNA isolated from hair (3.34 ± 1.7) and the DNA isolated from nails (4.36 ± 3.02). Analysis of MiniFiler results revealed that most of hair samples generated partial DNA profile while all samples of nail produced full profile and the percentage of allele’s appearance for hair samples range between (30%-90%). Whereas, nail samples alleles appearance was 100%. Conclusion, although both nail and hair tissues are subject to DNA fragmentation due to their keratinized structure and cellular composition, nail samples produces more consistent and complete DNA profiles compared to hair samples when analyzed using MiniFiler kit. This is likely attributed to the relatively lower degradation and greater stability of DNA in nails. In contrast, hair samples especially those lacking follicles exhibited a high degree of allele drop-out, particularly in loci with large amplicon sizes.